A Solar Tracker Using Commercial Components - Velkovski, Blagoja; Spasev, Vlatko (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
With a growing global population putting a strain on our energy resources, alongside unpredictable natural and geopolitical factors. Building a stable source of power has been at the forefront of research. Solar trackers are part of the solution. We will take a practical look at solar trackers in general, and we will present a custom-made solar tracker built from commercially available components controlled by dedicated control software.
Keywords: Robotics, Photovoltaics, Renewable Energy, Potential, Functions